Endothelial cell culture model for replication of physiological profiles of pressure, flow, stretch, and shear stress in vitro - Estrada, Rosendo; Giridharan, Guruprasad A; Nguyen, Mai-Dung; Roussel, Thomas J; Shakeri, Mostafa; Parichehreh, Vahidreza; Prabhu, Sumanth D; Sethu, Palaniappan (Analytical chemistry (Washington), 2011)
The phenotype and function of vascular cells in vivo are influenced by complex mechanical signals generated by pulsatile hemodynamic loading. Physiologically relevant in vitro studies of vascular cells therefore require realistic environments where in vivo mechanical loading conditions can be accurately reproduced. To accomplish a realistic in vivo-like loading environment, we designed and fabricated an Endothelial Cell Culture Model (ECCM) to generate physiological pressure, stretch, and shear stress profiles associated with normal and pathological cardiac flow states. Cells within this system were cultured on a stretchable, thin (∼500 μm) planar membrane within a rectangular flow channel and subject to constant fluid flow. Under pressure, the thin planar membrane assumed a concave shape, representing a segment of the blood vessel wall. Pulsatility was introduced using a programmable pneumatically controlled collapsible chamber. Human aortic endothelial cells (HAECs) were cultured within this system under normal conditions and compared to HAECs cultured under static and "flow only" (13 dyn/cm(2)) control conditions using microscopy. Cells cultured within the ECCM were larger than both controls and assumed an ellipsoidal shape. In contrast to static control control cells, ECCM-cultured cells exhibited alignment of cytoskeletal actin filaments and high and continuous expression levels of β-catenin indicating an in vivo-like phenotype. In conclusion, design, fabrication, testing, and validation of the ECCM for culture of ECs under realistic pressure, flow, strain, and shear loading seen in normal and pathological conditions was accomplished. The ECCM therefore is an enabling technology that allows for study of ECs under physiologically relevant biomechanical loading conditions in vitro.